The impact of Maize (Zea mays L.) and it uses for human development: A review - Monday Sunday Adiaha (International Journal of Scientific World, 2017)
Corn possesses significances nutrients, minerals and vitamins, which provides nutrition in animal diet as well as man. Its health benefits have been countless since the prehistoric era. Maize has been revealed to have the potential to sustained human health-related cases, raise standard of living of farmers, served as a soil fertility indicator crop, generate income and increase food-crop production for the increasing human population. Industrial utilization of maize has been shown to include: wet milling, production of bio-fuel, ethanol and other sub-byproducts. – – Mais enthält wichtige Nährstoffe, Mineralien und Vitamine und ist somit sowohl für die Ernährung von Tieren als auch von Menschen geeignet. Seine gesundheitlichen Vorteile sind seit prähistorischen Zeiten zahllos. Mais hat das Potenzial, menschliche Erkrankungen zu lindern, den Lebensstandard der Bauern zu erhöhen, als Indikator für die Bodenfruchtbarkeit zu dienen, Einkommen zu generieren und die Produktion von Nahrungsmitteln für die wachsende Weltbevölkerung zu steigern. Die industrielle Nutzung von Mais umfasst nachweislich: Nassmahlen, Produktion von Biokraftstoff, Ethanol und anderen Nebenprodukten.
Keywords: 630; Corn Silk; Maize Utilization; Maize Varieties; Nutrient Indicator; Zea Mays